Development and Use of A Research Database Management System - Sharifah Nurulhuda Tuan Mohd Yasin; Mastura Ramli (Journal of Counseling and Educational Technology, 2021)
Research Database Management System is refer to data transmission and storage of article sent by user of Politeknik Sultan Mizan Zainal Abidin (PSMZA). The problem statement are user takes advantage to their colleague for send article and at the same time they have been make plagiarism. Next, difficulty in making any dealings. Finally, difficulties in journal delivery are made systematically. Objective this project are to design of an online article data transmission system that has various interfaces that have various functions of their own. Next, to develop a database system that can receive article submissions from PSMZA user’s online. Finally, to access the article delivery application from offline to online. Methodology that be used is Software Development Life Cycle (SDLC) Technology”. In conclusion, this technique may facilitate the transfer of articles to UPIK team.